Impact of increasing antarctic glacial freshwater release on regional sea-ice cover in the Southern Ocean. (January 2018) - Merino, Nacho; Jourdain, Nicolas C.; Le Sommer, Julien; Goosse, Hugues; Mathiot, Pierre; Durand, Gael
Highlights: Impact of glacial freshwater on sea ice is studied with a sea ice/ocean/iceberg model. Ice shelves mass change is included for the first time in the freshwater perturbation. Changes in freshwater input increase sea ice cover with distinctive regional pattern. Impact of freshwater on sea ice volume is comparable to atmosphere-induced changes. Freshwater can decrease sea ice in Amundsen sector through ocean vertical circulation. Abstract: The sensitivity of Antarctic sea-ice to increasing glacial freshwater release into the Southern Ocean is studied in a series of 31-year ocean/sea-ice/iceberg model simulations. Glaciological estimates of ice-shelf melting and iceberg calving are used to better constrain the spatial distribution and magnitude of freshwater forcing around Antarctica. Two scenarios of glacial freshwater forcing have been designed to account for a decadal perturbation in glacial freshwater release to the Southern Ocean. For the first time, this perturbation explicitly takes into consideration the spatial distribution of changes in the volume of Antarctic ice shelves, which is found to be a key component of changes in freshwater release. In addition, glacial freshwater-induced changes in sea ice are compared to typical changes induced by the decadal evolution of atmospheric states. Our results show that, in general, the increase in glacial freshwater release increases Antarctic sea ice extent. But the response is opposite in some regions like the coastal Amundsen Sea, implying that distinct physical mechanisms are involved in the response. We also show that changes in freshwater forcing may induce large changes in sea-ice thickness, explaining about one half of the total change due to the combination of atmospheric and freshwater changes. The regional contrasts in our results suggest a need for improving the representation of freshwater sources and their evolution in climate models.